Mechanical and thermo-electrical properties evaluation of helical multiwall carbon nanotube enhanced carbon composite / Ali Naem S Alamry - Ali Naem , S Alamry (2022)
The introduction of carbon nanotubes (CNTs) inside a polymer matrix is preferred as a reinforcing medium to enhance the mechanical, physical, and electrical properties of composite materials. It was therefore the purpose of this study to experimentally investigate the role of helical multi-walled carbon nanotubes (HMWCNTs) on the fracture behavior of polymer composites and understand the underlying failure mechanisms under monotonic and impact loading conditions. Nanocomposite laminates were manufactured and subjected to various mechanical, thermal, and electrical tests to evaluate their properties. This was followed by a detailed examination of the fracture surface with the help of a field emission scanning electron microscope (FESEM) and ultrasonic C-scanning to investigate the underlying fracture and damage mechanisms. It was found that there was an increase in the mechanical strength of the nanocomposite laminates with the addition of HMWCNTs in comparison with the control sample. From the morphology analysis of fractured surfaces by FESEM, it was also found that upon increasing the number of HMWCNTs in the composite laminate, a higher bridging effect was achieved, which enhanced the strength of the composite laminates. Evidence that fewer HMWCNTs aggregated over the fracture surface was also found in this work.